Bifidobacterium animalis ssp. lactis BX-245-fermented milk alleviates tumor burden in mice with colorectal cancer - Chengcong Yang; Musu Zha; Lu Li; Jiaqi Qiao; Lai-Yu Kwok; Dandan Wang; Yongfu Chen (Journal of Dairy Science)
ABSTRACT: Colorectal cancer (CRC) arises from the accumulation of abnormal mutations in colorectal cells during prolonged inflammation. This study aimed to investigate the potential of probiotic fermented milk containing the probiotic strain, Bifidobacterium animalis ssp. lactis BX-245 (BX-245), in alleviating tumor burden in CRC mice induced by azoxymethane and dextran sodium sulfate. The study monitored changes in tumor size and number, gut microbiota, metabolomics, and inflammation levels before and after the intervention. Our findings indicate that intragastric administration of BX245-fermented milk effectively modulated the intratumor microbiota, as well as the gut microbiota and its metabolism. We also observed a decreased relative abundance of intratumor Akkermansia in the CRC mice, while the intratumor Parabacteroides exhibited a significant positive correlation with tumor number and weight. Moreover, administering BX245-fermented milk significantly reduced gut barrier permeability, alleviated gut barrier damage, and increased serum IL-2 and IFN-γ levels compared with the ordinary fermented milk group. Collectively, our data suggest that administering probiotic fermented milk containing specific functional strains such as BX245 could result in a reduction in tumor burden in CRC mice. Conversely, ordinary fermented milk did not show the same tumor-inhibiting effects. The current results are preliminary, and further confirmation is necessary to establish the causal relationship among probiotic milk, changes in gut microbiota, and disease alleviation.